THE USE OF FREE WRITING TECHNIQUE IN TEACHING WRITING NARRATIVE TEXT - Tina Apriyanti (Journal of English Education Program (JEEP), 2019)
This paper deals with the analysis of free writing technique in teaching writing narrative text. This study was aimed at investigating the implementation of ree writing technique in teaching writing narrative text, the problem encountered by the teacher in applying free writing technique and the teacher’s way in solving the problems occured in implementing free writing technique. Besides, the writer used a case study design as a research design of the study in order to gained the detail information of free writing technique in teaching writing narrative text. Meanwhile, the population in this study was the entire English teacher in a senior high school consisted of six English teachers. The sample of this study was an English teacher in a senior high school who taught writing narrative text through free writing. In determining the sample, the writer used purposive sampling technique. The instruments used in this study consisted of two instruments including classroom observation and interview. The results of data analysis showed that there were some steps conducting by the teacher in teaching English free writing technique. The first one was explaining the material of narrative text. The second one, after the students understood the material, the teacher encouraged the students to write freely in the groups. The last one, after the students were able to write in groups, the teacher encouraged the student to write a narrative text individually with the role of free writing technique. the teacher found difficulties in answering students’ question about the vocabulary that the students did not know. Furthermore, in solving the problem, the teacher encouraged the students to open the dictionary firstly before asking the words to the teacher. In conclusions, the teaching-learning process of writing throuh free writing technique is unfamiliar in Indonesia. It is somethings new for the indonesian teachers. Despite, its advantages of the implementation of free writing technique in the teaching-learning process gives contributions to the students’ development especially toward students’ achievement in writing. The study suggested to the English teacher, the students and also the researcher for further study. Besides, the further researchers are suggested to use various research instruments to gain the richer data.